Disease burden and treatment history among adults with atopic dermatitis receiving systemic therapy: baseline characteristics of participants on the EUROSTAD prospective observational study - Bruin-Weller, Marjolein de; Pink, Andrew E; Patrizi, Annalisa; Gimenez-Arnau, Ana M; Agner, Tove; Roquet-Gravy, Pierre-Paul; Ferrucci, Silvia M; Arenberger, Petr; Svensson, Ake; Schuttelaar, Marie L A; Nosbaum, Audrey; Jayawardena, Shyamalie; et al. (The Journal of dermatological treatment, 2021)
BACKGROUND: Insights into the real-world treatment paradigm and long-term burden of atopic dermatitis (AD) are needed to inform clinical and health policy decisions. METHODS: The prospective, observational EUROSTAD study enrolled adults with moderate-to-severe AD starting or switching systemic therapy (51 sites in 10 European countries). We report the baseline characteristics, treatment patterns, and outcomes of these patients using descriptive statistics. RESULTS: A 12-month enrollment period of EUROSTAD was completed and 308 patients were enrolled: average age 37 years, AD duration 25 years, 43% were female. Most patients reported use of systemic therapy (93%) and ≥1 atopic comorbidity (82%). Mean [standard deviation] disease severity/burden measures were high: Investigator's Global Assessment (3.1 [0.8]), Eczema Area and Severity Index (16.2 [10.9]), Peak Pruritus Numerical Rating Scale (5.5 [2.5]), sleep impairment Visual Analog Scale (49.8 [31.6]) scores, and time lost from work (4.1 [13.7] days/year) or usual activities (16.8 [38.7] days/year). Most patients showed borderline or clinical levels of anxiety (59%) and/or depression (63%) using the Hospital Anxiety and Depression Scale. CONCLUSIONS: Adults with moderate-to-severe AD starting/switching systemic treatment enrolled in EUROSTAD have a high burden of longstanding disease despite continuous use of topical drugs, emollients, and systemic therapies.
Keywords: quality of life; dospělí; Atopic dermatitis; Prospective Studies; senioři nad 80 let; cyklosporin; Humans; Prevalence; dermatologické látky; lidé středního věku; prospektivní studie; Aged, 80 and over; Middle Aged; Young Adult; mladý dospělý; systemic therapy; Cyclosporine; Comorbidity; Dermatitis, Atopic; komorbidita; mužské pohlaví; patient-reported outcomes; Severity of Illness Index; stupeň závažnosti nemoci; Adult; Adolescent; osobní újma zaviněná nemocí; ženské pohlaví; atopická dermatitida; lidé; mladiství; prevalence; Dermatologic Agents; Cost of Illness; Aged; Adrenal Cortex Hormones; hormony kůry nadledvin; senioři; Male; Quality of Life; kvalita života; Female